Slow dimer dissociation of the TATA binding protein dictates the kinetics of DNA binding - Coleman, Robert A. (The National Academy of Sciences of the USA, 1997)
The association of the TATA binding protein (TBP) to eukaryotic promoters is a possible rate-limiting step in gene expression. Slow promoter binding might be related to TBP’s ability to occlude its DNA binding domain through dimerization. Using a “pull-down” based assay, we find that TBP dimers dissociate slowly (t½ = 6–10 min), and thus present a formidable kinetic barrier to TATA binding. At 10 nM, TBP appears to exist as a mixed population of monomers and dimers. In this state, TATA binding displays burst kinetics that appears to reflect rapid binding of monomers and slow dissociation of dimers. The kinetics of the slow phase is in excellent agreement with direct measurements of the kinetics of dimer dissociation.